The marginal propensity to earn, consume and save out of unearned income in South Africa - Niklas Bengtsson (Uppsala University, Department of Economics, 2010)
We use a rapid introduction of an unconditional cash grant (child support) in South Africa to estimate the marginal propensity to consume and earn out of a permanent change in unearned income. We find that the marginal propensity to earn is about to -0.25 for single-adult households, and somewhat lower for households with more than one adult. A very small fraction of the grant is saved. All in all, the marginal propensities estimated here are all similar to those reported in comparable papers using US data. However, they stand in contrast to some results on conditional cash transfers in other developing countries.
urn:nbn:se:uu:diva-121603
Keywords: J22; O23; H31; 330; Social policy; Poverty reduction; Labor Supply; Earnings; Savings; Expenditure; Stone-Geary utility; Öffentliche Sozialleistungen; Armutspolitik; Haushaltsökonomik; Arbeitsangebot; Südafrika